PENGARUH PEMBAYARAN DIVIDEN TERHADAP KUALITAS LABA - Fiki Fiki; Indira Januarti (Diponegoro Journal of Accounting, 2017)
This study aims to examine the influence of dividend payment on earnings quality. Measuring the quality of earnings in this study is proxied by the ADA (Absolute Value of performanced-Adjusted Dicretionary Accruals) which is based on research Kothari (2005). This study uses four control variables, they are firm size, external growth prospect, internal growth prospect, and debt structure. The population in this study consist of all listed firms in Indonesia Stock Exchange in years 2011-2015. Sampling method in this study is purposive sampling. The total sample in this study are 203 sample. Analysis technique that used in this study is multiple regression. The empirical result of this study show that dividend payment have no effect on earnings quality as indicated by higher ADA. It means, companies that pay dividends have lower earnings quality.